Preparation of Ni3Fe2@NC/CC Integrated Electrode and Its Application in Zinc-Air Battery - Hu, Hui; Ling, Xiaofei; Tan, Chaogui; Lin, Jianguo; Han, Xiaopeng; Hu, Wenbin (Frontiers in Chemistry, 2020)
Reasonable design and development of a low-cost and high-efficiency bifunctional electrocatalyst for oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) is essential for promoting the development of Zinc-air battery technology. Herein, we obtained a Ni3Fe2@NC/CC integrated electrode by pyrolysis of bimetallic NiFe MOF uniformly supported on carbon cloth. There is a synergistic effect between nickel and iron, which enhances the bifunctional catalytic activity. In addition, the integrated electrode is conducive to the uniform loading of catalytically active substances. The integrated electrode shows good OER/ORR dual-functional catalytic performance, and the OER overpotential is much lower than that of the traditional drop-coating electrode and a precious metal catalyst. Moreover, the Ni3Fe2@NC/CC integrated electrode used in Zinc-air batteries shows good flexibility and cycle stability. Our findings provide a new avenue for the development of efficient and stable bifunctional oxygen electrocatalysts.